Blood flow restriction therapy for revolutionizing musculoskeletal rehabilitation and fitness: A comprehensive review - Jahanara Ayaz; Tamjeed ghaffar; Ahmad Bilal; Muhammad Mahmood Ali; Hamail Ayaz (Journal of Orthopaedic Reports)
Background: Blood flow restriction (BFR) is becoming increasingly common in rehabilitation to enhanced and target muscle growth, improved neuromuscular control, and produce less pain. However, the synergistic effects of BFR in individuals are yet to be unknown in musculoskeletal disorders. Objective: The aim of the study is to investigate the effectiveness of BFR exercises on pain relief, muscle growth, rehabilitation, and its current clinical applications. Methods: A systematic review with meta-analysis was carried out across six electronic databases: Web of Science, Google Scholar, Scopus, PubMed, CINAHL, and SPORT discus. Forty-seven clinical studies that examined LLR training with BFR for musculoskeletal disorders were included. Results: Evidence from the selected studies support the effectiveness of BFR in increasing muscle strength and mass for musculoskeletal disorders. The integration of BFR with traditional Low load training methods appears to enhance performance and health outcomes. Conclusion: Blood flow restriction therapy could offer a potent strategy for accelerating muscle growth and strength enhancement, as well as overall fitness improvements. However, more research is needed to determine the optimal occlusion pressure and application techniques for these therapies.